Procurement at local government level - Kaštelan-Mrak, Marija (Mednarodna revija za javno upravo, 2016)
Local government, as administrative units, performs a broad range of services that require to establish relations with outside partners, including those belonging to the private sector. Public procurement, due to the size of the involved financial flows, is government activity especially exposed to inefficiencies, corruption and dishonesty. There is an everlasting discussion on the ideal size and the range of services to be kept %in-house% of local government units (LGUs).Transaction Costs Economics (TCE) represents a theoretical paradigm specially designed to interpret the issue of efficiency in inter-institutional relations. However, even though TCE might be envisaged as a tool for building better systems and institutions, practical experience suggests that efficient organization of complex multi-institutional systems is still a goal to be met. Therefore, public procurement procedures at LGU level are suitable to analyze the transaction costs. In an attempt to determine the main organizational features of the existing scope of institutions/entities involved in delivering services to citizens, we provided an overview of the complexity of inter-organizational relations at LGU level. In this paper we present results of an empirical research of public procurement procedures from the perspective of LGUs in Croatia. Picking up on questionnaire responses from 200 LGUs that reported having held over 350 cases of providing services through contract agreements with %independent% service providers, we formed an opinion of what could be the consequences of developing more structured public procurement procedures.
Keywords: economic efficiency; ekonomska učinkovitost; javna naročila; javna uprava; local government; lokalna samouprava; public administration; public procurement; transaction costs; transakcijski stroški